Toys as tools for good science - LUCZAK, Joshua (Institutional Knowledge at Singapore Management University, 2023)
The primary aim of this paper is to elevate the status of toy models, toy model based reasoning, and to encourage more focused discussions of them. This paper attempts to satisfy this aim by achieving two, secondary goals. First, it attempts elevate the status of toy models by making clear and elaborating on the distinction between them and representational models, and by discussing the connection between user intentionality and scientific representation (i.e. when a model represents something). And second, this paper attempts to elevate the status of toy models by highlighting, through some important historical examples, how they have been used to do good science—despite the fact, that is, that they do not perform a representational function.